Delay-aware DWT-based image transmission in wireless visual sensor networks - Costa, Daniel G.; Guedes, Luiz Affonso; Vasques, Francisco; Portugal, Paulo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2013: Proceedings of the 19th Brazilian Symposium on Multimedia and the Web, 2013)
Wireless sensor networks have been employed as an effective tool for a large set of monitoring applications, directly supporting applications not addressed by conventional Internet-based technologies. Camera-enabled sensors enhance the applicability of those networks allowing innovative visual monitoring functions. Sometimes, source nodes will perform real-time monitoring of an area of interest, where visual data packets will need to be transmitted with minimum delay. However, energy depletion of the nodes that compose the transmission paths may hamper the network capability to deliver packets with time constraints. In such context, we propose a delay-aware image transmission mechanism where the relevancies of DWT subbands are considered when forwarding packets to the next hop toward the sink. In fact, parts of DWT-based encoded visual data may have different relevancies for the reconstruction of the original visual information and those relevancies may be exploited when forwarding packets. In the proposed approach, high-relevant packets are forwarded through paths with lower average end-to-end delay, while the remaining packets flow through paths high higher delay, allowing that low-quality versions of the transmitted images reach the sink as soon as possible. Moreover, the best paths will need to relay fewer packets, potentially reducing energy consumption and enlarging their lifetime. We present simulation results to attest the benefits of the proposed mechanism.